PENGARUH PENERAPAN STANDAR AUDIT TERHADAP RELIABILITAS LAPORAN AUDIT (SURVEY PADA KAP YANG BERADA DI JAKARTA UTARA) - Anggel Anggel; Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
Many founded audit report that not suitable in the fact on bussiness world. The purpose of this research is want to examine influence in  implementation of audit standard and reliability audit report ( Survey at Accountant Public Office in Nort of Jakarta).This research make use of deskriptif assosiatif method with utilized technic anlysis datas are simple linier regresion, F-test and T - test.The result of this research that the increase in implementation audit standard have positif effect and significant about increase in reliability audit report at Accountant Public Office in Nort Jakarta.  Keywords :  Implementation Audit Standard, Reliability Audit Report